TINJAUAN YURIDIS KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM PENYELESAIAN SENGKETA KONSUMEN (Studi Putusan Nomor 523 K/Pdt.Sus-BPSK/2020) - Tiara Aoura Sari; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The norms in consumer protection law are the consumer protection lawsystem as an "umbrella law" which becomes the criteria for measuringallegations of violations of consumer rights, which were originally expected byall parties to be able to provide solutions for resolving cases that arise. as theimplementation of the law. It turned out that in its application there was animbalance and caused confusion for the parties involved in the implementationprocess, especially when the role of the court was entered in examining objectioncases to the Consumer Dispute Settlement decision which experienced manyobstacles caused by aspects related to the Civil Procedure Code. It must beadmitted that the regulation on Consumer Dispute Settlement authority is stillnot well-organized because it is still here and there and causes problems bothfrom a theoretical and implementation perspective in the field.This type of research can be classified as normative legal research,because the research is conducted by examining library materials or secondarydata. The data sources used are primary data, secondary data, tertiary data,data collection techniques in this study are normative law, data analysis usingdescriptive analysis.The results of the research conducted by the author are the authority of theConsumer Dispute Settlement Agency based on Law Number 8 of 1999concerning Consumer Protection, namely handling and resolving consumerdisputes which are carried out by means of mediation, consulation andarbitration. Decision of the Supreme Court Number 523 K/Pdt.Sus-BPSK/2020reviewed based on Law Number 8 of 1999 concerning Consumer Protection isthat the Consumer Dispute Settlement Agency as an institution mandated toresolve consumer disputes outside the court does not carry out its duties andauthorities properly based on Law Number 8 of 1999 concerning ConsumerProtection because what is under the authority of the Consumer DisputeSettlement Agency is an unlawful act, not a civil dispute.Keywords: Juridical Review, Consumer Protection, BPSK Authority